International relations between the two World Wars, 1919-1939 - Carr, E.H. (Hampshire : Macmillan, 1937)
First published in 1937 under the title "International Relations since the Peace Treaties." Reissued 1947 as "International Relations between Two World Wars 1919-1934."
Keywords: International relations; World politics -- 1919-1932.; World politics -- 20th century